A comprehensive presentation to XACML - Abd El-Aziz, A.A; Kannan, A (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
XACML is an XML-based language for access control that has been standardized by OASIS (Organization for the Advancement of Structured Information Standards). XACML describes both an access control policy language that are ABAC and an access control decisions (request/response) language. Although XACML is recognized as a precise and complete policy description method, the structure of an XACML policy is complex and users need to understand XACML well and writes down the verbose policy all by hand, which make XACML difficult to master and use. In this paper, we present a comprehensive description of XACML to support the future research and development work.